Patterns of Protective Factors in an Intervention for the Prevention of Suicide and Alcohol Abuse with Yup'ik Alaska Native Youth - Henry, David; Allen, James; Fok, Carlotta Ching Ting; Rasmus, Stacy; Charles, Bill (Informa Healthcare, 2012)
© 2012 Informa Healthcare available at informahealthcare.com/journal/ada Community-based participatory research (CBPR) with American Indian and Alaska Native communities creates distinct interventions, complicating cross-setting comparisons. In this study, coding CBPR intervention activities from three communities for protective factors and latent class analysis identified five patterns of exposure to protective factors: Internal, External, Limits on alcohol, Community and family, and Low probabilities of all protective factors. Patterns differed significantly by community and youth age. Standardizing protective factors by the functions an intervention serves instead of its form or components can assist in refining CBPR interventions and evaluating effects in culturally distinct settings.